Peranan Motivasi Kerja dalam Kinerja Pegawai pada Kantor Kecamatan Tanjungbalai Utara Kota Tanjung Balai - Sinaga, Asmah Syam; Kadir, Abdul; Mardiana, Siti (Universitas Medan Area, 2020)
Aim of scope this research is analysis the role of work motivation in employee performance in Tanjung Balai North Tanjungbalai District office Research method is a method used by researchers in collecting research data. In this study the method used is a qualitative research method which is a research method whose case study leads to a detailed and in-depth description of the portrait of what actually happens according to what is in the field of study. The results showed that the role of work motivation in employee performance in Tanjung Balai North Tanjungbalai District office that motivation is very influential is the work itself which it has if appropriate, but in reality there are still employees who find it difficult to carry out motivation due to the employee wanting to retire, this ditujukkan of employees in completing the work given is always not maximally done well, and the work given to employees in accordance with the expertise and ability of employees so that in the completion of the work will cause a feeling of dislike of the work with results that are not good too. So that it can be said that the work of the employee itself motivates them to work.